Application of classical land surveying measurement methods for determining the vertical displacement of railway bridges = Zastosowanie klasycznych metod geodezyjnych do wyznaczania przemieszczeń pionowych belek dźwigara mostu kolejowego - Gawronek, Pelagia; Makuch, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The classical measurements of stability of railway bridge, in the context of determining the vertical displacements of the object, consisted on precise leveling of girders and trigonometric leveling of controlled points (fixed into girders` surface). The construction elements, which were measured in two ways, in real terms belonged to the same vertical planes.
Keywords: determination of displacements; displacement of structure; deformation of structure; precise leveling; trigonometric leveling; steel railway bridge; wyznaczanie przemieszczeń; przemieszczenia obiektu; odkształcenia obiektu; niwelacja precyzyjna; niwelacja trygonometryczna; stalowy most kolejowy; metody geodezyjne